TO EVALUATE THE SOURCES OF BLUNT CHEST TRAUMA AND FREQUENCY OF CHEST COMPLICATIONS IN TRAUMATIC PATIENTS AT TERTIARY CARE HOSPITAL - Sajjad Hussain Qureshi1, Shahida Baloch2, Kashif Ali Shah3, Shahnawaz Laghari4, Naeem Bhatti5, Maimona Khushk6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
INTRODUCTION: Physical Trauma is the tragic and multifaceted injuries that could be life threatening. It is the 3rd most common cause of mortality in the globe. Most incidences is seen in first 4 decades of life throughout world. Blunt chest trauma is commonly caused by moving vehicles physical assault and falling from height also. Nowadays, world is facing this serious problem and is continuously increasing yearly in every country. Thoracic trauma occurs in 60% of polytrauma patients and has 20-25% mortality rate. OBJECTIVE OF STUDY: To determine the sources of Blunt trauma and the frequency if multiple injuries as a result of blunt trauma. STUDY DESIGN: Cross sectional study. PLACE AND DURATION OF STUDY: AT Surgical Unit-II PMC Hospital Nawabshah. Duration was from October 2019 to September 2020. PATIENTS AND METHODS:. All the patients were admitted with diagnosis of Blunt chest trauama from Trauma center PMC Hospital Nawabshah.. They were examined by applying ATLS and managed accordingly. Auscultation was done. Radiological investigations and biochemical workup was done. Focussed Assesment with Sonography in Trauma (FAST) was done immediately. The treatment was decided accordingly. RESULTS: Blunt trauma is caused by many sources. In our study, 44 (57%) patients got blunt injuries due to road traffic accident by bike, 20 (29%) by car, 8(10%) by fall from height and only 5(7%) by collapse of wall. Blunt chest trauma can injure many organs but the most vulnerable are lungs. Simple pneumothorax was seen among 34 (44.1%) patients and tension Pneumothorax in 5 (6.4%). Hemothorax was seen in 12 (15.5%) , surgical emphysema in 20(25.9%) and flail chest was noted in 6 (7.7%) patients. CONCLUSION: It is concluded that sources of blunt trauma commonly are moving vehicles both two wheeler oe four wheeler and the complication commonly developed are pneumothorax and surgical emphysema.